Beispiel Nr: 26
$ \text{Gegeben:} ax^{2}+bx+c=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ ax^{2}+bx+c=0 \\ \textbf{Gegeben:} \\ \frac{1}{2}x^2-1x+4 =0 \\ \\ \textbf{Rechnung:} \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \frac{1}{2}x^{2}-1x+4 =0\\ x_{1/2}=\displaystyle\frac{+1 \pm\sqrt{\left(-1\right)^{2}-4 \cdot \frac{1}{2} \cdot 4}}{2\cdot\frac{1}{2}}\\ x_{1/2}=\displaystyle \frac{+1 \pm\sqrt{-7}}{1}\\ \text{Diskriminante negativ keine Lösung} \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ \frac{1}{2}x^{2}-1x+4 =0 \qquad /:\frac{1}{2} \\ x^{2}-2x+8 =0 \\ x_{1/2}=\displaystyle -\frac{-2}{2}\pm\sqrt{\left(\frac{\left(-2\right)}{2}\right)^2-8} \\ x_{1/2}=\displaystyle 1\pm\sqrt{-7} \\ \text{Diskriminante negativ keine Lösung} \end{array}\\ \end{array}$